2011
DOI: 10.1210/jc.2010-0929
|View full text |Cite
|
Sign up to set email alerts
|

Twist1 in Human White Adipose Tissue and Obesity

Abstract: Low twist1 expression in human WAT correlates with obesity and an insulin-resistant phenotype, which may be mediated by an increased sensitivity to the proinflammatory effect of TNFα.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 32 publications
6
49
0
Order By: Relevance
“…mRNA and protein expression of Twist1 in human AT are lower in obese than non-obese individuals [15]. Moreover, it has been reported that low mRNA and protein expression of Twist1 is associated with increased expression of proinflammatory cytokines and decreased insulin sensitivity in humans [15]. In accordance with the latter study in human AT, we found gene expression of Twist1 to be significantly lower in the obese than the non-obese group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…mRNA and protein expression of Twist1 in human AT are lower in obese than non-obese individuals [15]. Moreover, it has been reported that low mRNA and protein expression of Twist1 is associated with increased expression of proinflammatory cytokines and decreased insulin sensitivity in humans [15]. In accordance with the latter study in human AT, we found gene expression of Twist1 to be significantly lower in the obese than the non-obese group.…”
Section: Discussionsupporting
confidence: 89%
“…In humans, Twist1 is expressed mainly in adipocytes of AT, but not in the liver, pancreas or skeletal muscle [31]. mRNA and protein expression of Twist1 in human AT are lower in obese than non-obese individuals [15]. Moreover, it has been reported that low mRNA and protein expression of Twist1 is associated with increased expression of proinflammatory cytokines and decreased insulin sensitivity in humans [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α release from abdominal subcutaneous WAT (scWAT) was determined as described [23]. In short, WAT explants were incubated for 2 h after which TNF-α secretion into medium was quantified with ELISA (R&D Systems, Minneapolis, MN, USA) as ng per 10 7 adipocytes.…”
Section: Methodsmentioning
confidence: 99%
“…TWIST1 expression in Thelper 1 (T H 1) lymphocytes and bone marrow-derived macrophages attenuates the expression of IFN-g, interleukin (IL)-2, and TNF-a, further implicating TWIST1 in the regulation of cytokine expression (25)(26)(27). It was also reported that CCL2 expression may be subject to regulation by TWIST1 (28). The relationship between androgens and these EMT-related proteins as well as the relation between TWIST1 and CCL2 in prostate cells remains unresolved.…”
Section: Introductionmentioning
confidence: 99%